Wasatiyyah Dalam Konsep Takdir dan Hubungannya dengan Pengurusan Stres: Wasatiyyah In The Concept Of Fate And Its Relationship With Stress Management - Syed Abdul Rahman, Syed Mohammad Hilmi; Mohd Azhar, Muhammad Hazim; Mohd Khambali @ Hambali, Khadijah; Sa’ari, Che Zarrina; Zainal Abidin, Azmil; Wan Ramli, Wan Adli; Che Nordin, Mohd Khairul Naim; Mamat, Mohd Anuar; Abd. Latif, Faizuri; Gobaili Saged, Ali Ali (Online Journal of Research in Islamic Studies, 2020)
Faith in destiny is one of the criterion of a Muslim’s faith. However, the question of destiny is often questioned and debated to the point of producing two conflicting extreme streams, namely the Qadariah stream and the Jabariah stream. The Qadariah stream focuses on the authority of humans will and deeds to deny destiny. Jabariah, on the other hand, is an extremist in condemning destiny to the point of denying the existence of freedom of will and human actions. In the meantime, the stream of Ahl al-Sunnah wa al-Jama`ah was born, adapting the middle path (wasatiyyah) in convicting destiny. True belief and understanding of the concept of destiny is not only a proof of the faith of a Muslim, but it is also the ability to produce a constant positive attitude in oneself to exist in the world whether in pleasure or hardship. This paper aims to examine the beliefs of wasatiyyah in convicting destiny and its role in overcoming the problem of stress by referring to the views of Ahl al-Sunnah wa al-Jama`ah who applies the theory of al-Kasb in the discussion of destiny. While al-Ghazali theory that uses the approach of al-â€˜Aql, al-Qalb, al-Ruh and al-Nafs in stress management. The findings of this discussion show that the mind is capable in managing stress with the support of spiritual aspects. It is regarded that human beings do not have absolute power, everything is under the will and Will of God, but every individual must have effort and initiatives. Thus, these efforts and endeavors encourage individual not to boast shamelessly in times of successful efforts and not to give up in times of failure. Ultimately, reliance on ikhtiar with high confidence in Allah encourages individual to compose oneself and successfully manage stress efficiently even when one is trying the impossible because of the immense notion that it is worth doubling their efforts and ikhtiar.